Effects of α-synuclein overexpression in transgenic Caenorhabditis elegans strains - Bodhicharla, Rakesh; Nagarajan, Archana; Winter, Jody; Adenle, Ademola; Nazir, Aamir; Brady, Declan; Vere, Kelly; Richens, Jo; O'Shea, Paul; Bell, David R.; de Pomerai, David I. (Bentham Science Publishers, 2012)
The neural protein α-synuclein aggregates both in vivo and in vitro to form insoluble fibrils that are involved in Parkinson’s disease pathogenesis. We have generated α-synuclein/fluorescent-protein fusion constructs overexpressed in muscle cells of the nematode, Caenorhabdtis elegans. Green Fluorescent Protein (GFP) variants, Cerulean (C) or Venus (V), were fused to the C-terminus of human α-synuclein (S); the resultant fusion genes were designated SV and SC, plus a CV fusion as well as S, C and V singly. The aggregation behavior of the purified fusion proteins (expressed in E. coli) will be described elsewhere. These constructs were fused to a C. elegans unc-54 myosin promoter, and integrated transgenic lines generated by microinjection, gamma-irradiation, and outcrossing of fluorescent progeny. All transgenic lines expressing α-synuclein showed significant reductions (p < 0.05) in lifespan, motility and pharyngeal pumping, as compared to wildtype worms or lines expressing CFP and/or YFP only. We showed that CFP and YFP labels colocalised in granular inclusions throughout the body wall in transgenic lines expressing both SC and SV fusions (SC+SV), whereas SV+C worms.